VEGF dose controls the coupling of angiogenesis and osteogenesis in engineered bone - Grosso, Andrea; Lunger, Alexander; Burger, Maximilian G.; Briquez, Priscilla S.; Mai, Francesca; Hubbell, Jeffrey A.; Schaefer, Dirk J.; Banfi, Andrea; Di Maggio, Nunzia (npj Regenerative medicine, 2023)
Vascular endothelial growth factor-A (VEGF) physiologically regulates both angiogenesis and osteogenesis, but its application in bone tissue engineering led to contradictory outcomes. A poorly understood aspect is how VEGF dose impacts the coordination between these two processes. Taking advantage of a unique and highly tunable platform, here we dissected the effects of VEGF dose over a 1,000-fold range in the context of tissue-engineered osteogenic grafts. We found that osteo-angiogenic coupling is exquisitely dependent on VEGF dose and that only a tightly defined dose range could stimulate both vascular invasion and osteogenic commitment of progenitors, with significant improvement in bone formation. Further, VEGF dose regulated Notch1 activation and the induction of a specific pro-osteogenic endothelial phenotype, independently of the promotion of vascular invasion. Therefore, in a therapeutic perspective, fine-tuning of VEGF dose in the signaling microenvironment is key to ensure physiological coupling of accelerated vascular invasion and improved bone formation.